2021
DOI: 10.1007/s12020-021-02757-3
|View full text |Cite
|
Sign up to set email alerts
|

Beyond hemoglobin A1c: a videographic analysis of conversations about quality of life and treatment burden during clinical encounters for diabetes care

Abstract: Purpose: Diabetes care has largely focused on reducing the risk of complications by achieving hemoglobin A1c (HbA1c) targets; yet, whole-person care may be more effective and desirable. We sought to determine the nature of discussions about quality of life, burden of treatment, hypoglycemia, sexual function, and social support during diabetes-focused clinical encounters. Methods: We analyzed 41 previously recorded clinical encounters with patients with type 2 diabetes from the control arms of practice-based tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…Similarly, a prior qualitative study found that tasks such as implementing complex medication regimens and making lifestyle changes were burdensome for some people (16). Clinicians most often responded to conversation cards by asking elaborating questions, similar to results from our prior study assessing clinicians' responses to patients' concerns (5). These forms of problem-solving conversations demonstrate purposeful shared decisionmaking (17) and illustrate how shared decision-making can be an effective method for care (18).…”
Section: Feature Article Qbsafe Diabetes Agenda-setting Kitsupporting
confidence: 70%
“…Similarly, a prior qualitative study found that tasks such as implementing complex medication regimens and making lifestyle changes were burdensome for some people (16). Clinicians most often responded to conversation cards by asking elaborating questions, similar to results from our prior study assessing clinicians' responses to patients' concerns (5). These forms of problem-solving conversations demonstrate purposeful shared decisionmaking (17) and illustrate how shared decision-making can be an effective method for care (18).…”
Section: Feature Article Qbsafe Diabetes Agenda-setting Kitsupporting
confidence: 70%
“…The result of the thematic analysis represents a measurement framework for treatment burden in people with T2DM (Table 2 ). Seven themes had sufficient evidence to support their use as directly quantifiable indicators of the T2DM treatment burden, including financial [ 32 37 ], medication [ 35 , 36 , 38 , 39 ], administrative [ 33 , 35 38 , 40 , 41 ], lifestyle [ 33 , 34 , 36 , 37 , 39 , 41 , 42 ], healthcare [ 32 , 35 39 , 43 , 44 ], time/travel [ 32 , 33 , 36 , 43 ], and medical information [ 28 , 34 36 , 39 , 43 ], and were categorised as core measurement themes. Sub-themes reflecting the antecedents [ 32 , 36 , 39 , 41 , 45 ] (patient characteristics, living with T2DM) and consequences [ 32 , 33 , 35 37 , 41 ] (adherence to treatment, health and wellbeing and quality of life, interpersonal and social challenges) of the burden were encapsulated into associated measurement themes.…”
Section: Resultsmentioning
confidence: 99%
“…Seven themes had sufficient evidence to support their use as directly quantifiable indicators of the T2DM treatment burden, including financial [ 32 37 ], medication [ 35 , 36 , 38 , 39 ], administrative [ 33 , 35 38 , 40 , 41 ], lifestyle [ 33 , 34 , 36 , 37 , 39 , 41 , 42 ], healthcare [ 32 , 35 39 , 43 , 44 ], time/travel [ 32 , 33 , 36 , 43 ], and medical information [ 28 , 34 36 , 39 , 43 ], and were categorised as core measurement themes. Sub-themes reflecting the antecedents [ 32 , 36 , 39 , 41 , 45 ] (patient characteristics, living with T2DM) and consequences [ 32 , 33 , 35 37 , 41 ] (adherence to treatment, health and wellbeing and quality of life, interpersonal and social challenges) of the burden were encapsulated into associated measurement themes. Additionally, four novel themes related to T2DM treatment emerged, including health locus of control for T2DM treatment [ 33 , 34 , 36 , 37 , 41 , 43 ], insulin or injection-related burden [ 36 , 37 ], medication-related hypoglycaemia [ 28 , 34 ], and glucose meters [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…All components identi ed in the preliminary conceptual framework were consistently present, and four novel themes emerged from the thematic analysis (Table S3). Finances (28-33), medication (31,32,34,35), administrative (29, 31-34, 36, 37), lifestyle (29,30,32,33,35,37,38), healthcare (28, 31-35, 39, 40), time/travel (28, 29, 32, 39), and medical information (26, 30-32, 35, 39) were classi ed into CORE measurements. Sub-themes re ecting the antecedent (28, 32, 35, 37, 41) (patient characteristics, living with T2DM) and consequence (28, 29, 31-33, 37) (adherence to treatment, health and wellbeing and quality of life, interpersonal and social challenges) of treatment burden were encapsulated into these two themes.…”
Section: Conceptual Frameworkmentioning
confidence: 99%